-6+1= -5
1 + 6 + 9 - 8 + 4 - 5 + 2 + 3 = -6
15 + 6 - 1 = 20
-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3
+1.
8
minus 6, plus 3, minus 6, plus 3...
-6+1= -5
1 + 6 + 9 - 8 + 4 - 5 + 2 + 3 = -6
9A:2 - 1 - 1 + 1 - 1 + 3 - 2 + 6 = 7The answer is seven.
15 + 6 - 1 = 20
-4x-1-3x-4+5 = -7x-1-2x+1+6 -7x = -9x+6 2x = 6 x = 3
12.
+1.
A = 6
-8 - (-7 + 1) = -8 - (-6) = -8 + 6 = -2
x/2+1 = 2x/5-2 x/2+1 = 2x/3 Multiply all terms by 6 to eliminate the fractions: 3x+6 = 4x 3x-4x = -6 -x = -6 Divide both sides by -1 remembering that a minus number divided into a minus is equal to a plus: x = 6